Development of a laser complex for ecological monitoring of the atmosphere of urban and industrial areas - Titar, Vladimir; Shpachenko, Olga; Panimarchuk, Oksana; Guzenko, Mykhailo; Koshman, Sergii; Lutsky, Sergey (Technology audit and production reserves, 2020)
The object of research is methods of remote ecological monitoring of the surface layer of the atmosphere within residential areas and industrial zones of big cities. For the remote determination of the quantitative characteristics of gas and aerosol air pollution with high accuracy and spatial resolution, a mobile laser complex has been proposed. Determination of the composition and concentration of gas pollutants is carried out using two methods – the differential absorption method and the spontaneous Raman scattering (SRS) method. The differential absorption method is used to detect low concentrations of polluting gases along a stationary sounding path. The spontaneous Raman scattering method is used for remote detection of harmful gaseous substances at their concentrations exceeding the maximum permissible standards. SRS method used in the developed gas aerosol lidar allows one to obtain three-dimensional distributions of the concentrations of the gases being determined with a resolution of the order of one meter. This makes it possible to quickly and accurately identify environmentally hazardous sources of air pollution and reasonably apply penalties to violators of environmental standards. Remote analysis of the aerosol composition of the surface layer of the atmosphere is carried out using lidar holography methods, which were developed in the laboratory of radio and optical holography of V.N. Karazin Kharkiv National University (Ukraine). The difference in reflection from liquid and solid aerosol particles makes it possible to form polarization holograms and consider them separately for liquid and solid aerosols. Quantitative analysis of the composition and concentration of particles observed from their holographic images is characterized by a high level of sensitivity, since, unlike other known methods, it does not require a priori assumptions about the qualitative composition of the determined aerosol. Thus, due to the use of various physical principles of the interaction of laser radiation with gaseous and aerosol components of the air, the developed laser complex for environmental monitoring of the atmosphere is an effective means of monitoring the state of the air in the conditions of modern megacities.